Pelaksanaan dan Penatausahaan Pengelolaan Keuangan Daerah Pada Sekretariat Daerah Kota Mataram - Fitria Wahida; Animah Animah; Lalu Takdir Jumaidi (Universitas Teuku Umar, 2022)
Regional Financial Management includes the implementation and administration of bookkeeping as well as the accountability of the expenditure treasurer. This study was conducted to analyze: 1) Conformity of the Implementation and Administration of Expenditure Treasurer Bookkeeping in the General Section of the Regional Secretariat of Mataram City with Regional Financial Management and Minister of Home Affairs Regulation Number 77 of 2020, 2) Conformity of Implementation and Administration of Expenditure Treasurer Accountability in the General Section of the City Regional Secretariat Mataram with Regional Financial Management and Minister of Home Affairs Regulation Number 77 of 2020. The type of research used is qualitative with a descriptive approach. The method of data collection is done by interview, observation, and documentation to obtain primary and secondary data. The results showed that the implementation and administration of regional financial management at the Regional Secretariat of Mataram City, especially related to bookkeeping and the accountability of the expenditure treasurer was not fully in accordance with the Regulation of the Minister of Home Affairs Number 77 of 2020. The discrepancy lies in the implementation of the accountability report on the use of UP and TU by the expenditure treasurer and the submission of administrative and functional responsibilities. This discrepancy is caused by several factors, namely system changes, lack of socialization, late decision making, and human error.